Hepatitis B Virus Reactivation and Mycobacterial Infections Associated With Ustekinumab: A Retrospective Study of an International Pharmacovigilance Database - Wang, Jingjing; Geng, Xiaozhen; Zhang, Xin; Xiao, Yanfeng; Wang, Wenjun (Frontiers in Pharmacology, 2022)
Background: Reports were recently published on hepatitis B virus reactivation (HBVr), tuberculosis (TB), and atypical mycobacterial infection (AMI) in patients with ustekinumab treatment. However, the literature is limited to case reports and series. The study was aimed to investigate their relationships by using an extensive population-based database. Methods: Using the United States Food and Drug Administration Adverse Event Reporting System (FAERS) database, we collected all cases of HBVr, TB, and AMI between January 1, 2009 and September 30, 2021, for ustekinumab and other drugs. Disproportionality was analyzed using the reporting odds ratio (ROR), which was considered significant when the lower limit of the 95% confidence interval (95% CI) was >1. Results: Of the 18,760,438 adverse cases reported to FAERS for all drugs, 56,581 cases had been exposed to ustekinumab. Adverse events of HBVr, TB, and AMI were reported in 21, 210, and 20 cases, respectively. The ROR for HBVr with ustekinumab was 2.33 (95% CI, 1.52–3.58), for TB was 5.09 (95% CI, 4.44–5.84), and for AMI was 2.09 (95% CI, 1.35–3.24). In the ustekinumab exposure group, no death occurred in patients with HBVr, but one patient experienced life-threatening liver failure. For those with TB, 24 cases experienced hospitalization and 2 deaths occurred. No death occurred in patients with AMI but eight experienced hospitalization. Conclusion: We identified positive signals between ustekinumab exposure and HBVr, TB, and AMI in FAERS. Although these complications are rare, clinicians using ustekinumab should be aware of the risks.